CSC548: Distributed Multimedia / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2022)
The subject provides the students with an understanding of telecommunications and networking which is related to the design and implementation of multimedia applications on the network.